Development of compact circular polarized antenna for WLAN application - Ali Nor, Abdirahman Sidow (2019)
Matching the polarization in both the transmitter and receiver antennas is important in terms of decreasing transmission losses. The use of circularly polarized antennas presents an attractive solution to achieve this polarization match which allows for more flexibility in the angle between transmitting and receiving antennas, reduces the effect of multipath reflections, enhances weather penetration and allows for the mobility of both the transmitter and the receiver. Compact circularly polarized microstrip antenna with Circular Polarization (CP) property for wireless communication system at 2.45 GHz is presented. Microstrip patch antennas being popular because of light weight, low volume, thin profile configuration which can be made conformal. Wireless communication systems applications circular polarization antenna is placing vital role. In this study it was applied DGS to produce circular polarization. The single fed circular polarized microstrip antenna is etched on a FR4 with dielectric substrate of 4.3 with the height of 1.6 mm. The axial ratio of approximate 2.1 dB and the radiation pattern results prove that the designed antenna meets the CP criteria. The simulated and measured results show a good agreement and the proposed antenna is suitable for WLAN applications.